An Assessment Study on Consumer Knowledge and Purchasing Behavior Regarding Food Safety - , Sengul ULUDAG, Nermin BAHSI (Archives of Current Research International, 2024)
Economic and technological developments affect consumers’ purchasing behaviors along with their lifestyles. Understanding consumer characteristics and purchasing behaviors is of great importance for companies in determining target markets and preparing marketing programs. The aim of this study is to determine consumers’ level of knowledge about food safety and their purchasing behavior regarding food products. For this purpose, a face-to-face survey was conducted with 400 consumers selected using the Simple Random Probability Sampling method. About 76% of the consumers participating in the study have heard of the concept of food safety. It was found that consumers primarily consider health safety, the expiry date, and the cleanliness of the place of purchase when buying food products. They prefer the products they consume to be fresh and mostly shop at supermarkets and hypermarkets. It was also determined that 53.8% of consumers pay partial attention to human health conditions in the places where food is produced, and 69% are willing to pay more for packaged foods. The level of food safety knowledge among consumers will provide important feedback for food producers and policymakers, guiding the creation of more effective and safer food systems that address consumer needs.